(untitled) (Research, Society and Development, 2022)
Breast cancer screening in Brazil is carried out, as a priority, opportunistically, through mammographic examinations. The objective was to quantitatively describe the technology park available for breast cancer screening during mammography (MMs) and mammographic examinations (MMG). This is a quantitative study, which analyzed official and public access databases from 2015 to 2021. The number of MM in use is extracted from the National Registry of Health Establishments (CNES), despite the proportion of women served by health plans (PS), data from the National Supplementary Health Agency (ANS), and the estimation of the objective population (PA) of the Department of Informatics of the SUS (DATASUS), from which the number of SUS approved mammograms (MMG) is also extracted. It was concluded that there is an excess of MMs in use to serve the PA throughout Brazil and its regions, with the largest number in the Southeast and the smallest in the North. Among the Federation Units (UF), São Paulo had the highest number of devices in use. Acre, Roraima and Amapá presented the smallest number of devices in use of the SUS. As for the states with less MMs in use under the SUS, Roraima, Acre, Amapá and Tocantins stood out, all from 2015 to 2021, and Alagoas, in 2018. Of the UFs, they noted a lack of MMs to serve both populations, during some years of the analyzed period: Acre and Distrito Federal. The MMG exams approved by the SUS did not reach the coverage target of 50% of the PA ED.